Aberrant ROS Mediate Cell Cycle and Motility in Colorectal Cancer Cells Through an Oncogenic CXCL14 Signaling Pathway - Zeng, Jun; Li, Mei; Xu, Jun-Yu; Xiao, Heng; Yang, Xian; Fan, Jiao-Xiu; Wu, Kang; Chen, Shuang (Frontiers in Pharmacology, 2021)
Background: Reactive oxygen species (ROS) act as signal mediators to induce tumorigenesis. Objective: This study aims to exam whether chemokine ligand 14 (CXCL14) is involved in the proliferation and migration of ROS-induced colorectal cancer (CRC) cells. Methods: The proliferative and migratory capacities of CRC cells treated without or with H2O2 were measured by various methods, including the CKK-8 assay, colony formation assay, flow cytometry, wounding healing assay, and migration assay. Results: The results revealed that H2O2 promoted the proliferation and migration of CRC cells by regulating the cell cycle progression and the epithelial to mesenchymal transition (EMT) process. Furthermore, we noted that the expression level of CXCL14 was elevated in both HCT116 cells and SW620 cells treated with H2O2. An antioxidant N-Acetyl-L-cysteine (NAC) pretreatment could partially suppress the CXCL14 expression in CRC cells treated with H2O2. Next, we constructed CRC cell lines stably expressing CXCL14 (HCT116/CXCL14 and SW620/CXCL14) and CRC cell lines with empty plasmid vectors (CXCL14/Control and SW620/Control) separately. We noted that both H2O2 treatment and CXCL14 over-expression could up-regulate the expression levels of cell cycle-related and EMT-related proteins. The level of p-ERK was markedly higher in HCT116/CXCL14 cells when compared with that in HCT116/Control cells. In addition CXCL14-deficiency significantly inhibited the phosphorylation of ERK compared with control (i.e., scrambled shNCs). H2O2 treatment could partially restore the expression levels of CXCL14 and p-ERK in HCT116/shCXCL14 cells. Conclusion: Our studies thus suggest that aberrant ROS may promote colorectal cancer cell proliferation and migration through an oncogenic CXCL14 signaling pathway.